Evolution of Freshly Generated Equatorial Spread F (F-ESF) Irregularities on Quiet and Disturbed Days - Gurram, P.; Kakad, B.; Bhattacharya, A.; Pant, T. K. (My University, 2018)
We examined the seasonal and solar flux dependence of the occurrence of freshly generated intermediate scale (100 m to few km) equatorial spread F (ESF) irregularities during magnetically quiet (Q) and disturbed (D) periods. We utilized long-term (1992–2006 and 2013–2015) amplitude scintillation data on a 251 MHz signal recorded at Tirunelveli (dip lat. 1.5∘N ). Also, ionosonde data (1990–2003) recorded at Trivandrum (dip lat. 0.5∘N) are used. The presence of fresh ESF (F-ESF) is identified using the maximum cross-correlation between intensity variations recorded by two spaced receivers on a magnetic east-west baseline. We find distinct differences in the seasonal and solar flux dependence of the usual postsunset (<22 LT) generation of F-ESF on both Q- and D-days. Interesting feature is that F-ESF linked moderate–strong scintillations are more prevalent on D-days as compared to Q-days in both early (18–22 LT) and later (>22 LT) phase of evolution of the irregularities. It directly hints toward the difference in the spatial structuring (spatial scales) of F-ESF on D-days as compared to Q-days. On D-days, the occurrence of F-ESF is more likely around midnight and early-morning hours in all seasons. Whereas on Q-days, the postmidnight F-ESF is found to occur mainly during solstices of low solar activity. The possible sources for the generation of F-ESF around midnight on Q-days of solstices during low solar activity are examined. We also find that perturbation electric field linked with F-ESF on D-days sustains for longer time, which results in longer durations of the active phase of equatorial plasma bubbles.
Keywords: Equatorial spread F; Equatorial plasma bubbles; ESF; EPBs; F-ESF; Perturbation electric field